Evaluasi Nilai Diagnostic Reference Level (DRL) pada pemeriksaan CT Scan Thorax Kontras klinis tumor paru di RS X Jakarta - Yuly Ekayanti; Gando Sari; Muhammad Irsal; Heri Kuswoyo (Jurnal Teori dan Aplikasi Fisika, 2024)
A contrast thorax CT scan is a CT scan procedure in the chest area (thorax) that uses a contrast agent to improve visualization of organs and structures in the chest. Lung tumors are the growth of abnormal lumps in lung tissue which can be benign or malignant. Awareness of the potential and increasing radiation dose in all CT scan examinations encourages radiographers to want and be able to minimize radiation exposure as the main goal in radiological examinations and also strive for radiation protection during examinations. CT scan radiation dose accounts for 70% of the total dose received from medical imaging. High or low doses of radiation received can increase the risk of cancer. The large dose of radiation received by a patient during a CT scan, therefore regulations are needed that will guarantee monitoring of the radiation dose received by the patient to ensure that the dose received is commensurate with medical purposes. The radiation dose to the patient needs to be optimized by applying the Diagnostic Reference Level (DRL) to optimize medical exposure protection for the patient. Dosage evaluation in clinical contrast chest CT scan examinations for lung tumors and the application of DRL in these examinations have never been carried out at RS X Jakarta. Objective: This study aims to determine the DRL value in clinical contrast thorax CT scan examination of lung tumors at RS CTDIvol and DLP values from clinical contrast Thorax CT Scan examination of lung tumors. The DRL value is calculated at Quartile 3 (75 percentile) using the descriptive frequency test and Wilcoxon test in the SPSS application, then compared with the latest IDRL value. Results: Quartile 3 value (75 percentile) from CTDIvol and DLP CT scan chest contrast clinical lung tumors, namely The CTDIvol value was 12.55 mGy and the DLP was 439 mGy.cm. Conclusion: The DRL value in the clinical contrast thorax CT scan for lung tumors at Hospital X Jakarta. is still below the recommended standard, which shows that the radiation output dose in this examination practice is within normal limits and is classified as safe